Analisis Kemampuan Literasi Membaca Siswa Kelas VI dari Perspektif Guru Kelas VI SD: Penelitian - Puspita, Tri; Nizam, Sahrul; Rosyada, Asyafina; Wulandari, Rika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the reading literacy abilities of sixth-grade students at UPTD SDN Kamal 1 from the perspective of the classroom teacher, particularly regarding reading fluency, text comprehension, and the factors that influence these abilities. The research employs a qualitative method with a phenomenological approach, in which the researcher acts directly as the main instrument through observation activities, structured interviews, and the collection of supporting documents. The sixth-grade teacher serves as the research subject, while the aspects examined include students’ reading abilities as well as their interest and motivation in literacy activities. The results show that most students are able to read, yet still lack fluency in pronunciation and experience difficulties in understanding the meaning of the text. The teacher explains that low reading interest is the dominant factor hindering the development of literacy skills, as reflected in the students’ limited participation in reading activities both at school and at home. The observational findings support this, showing that several students appear passive, have low concentration, and struggle to answer questions related to the text. An unsupportive classroom atmosphere also affects the process of learning to read. Overall, the study indicates that students’ literacy skills remain focused on technical aspects without deeper comprehension. Therefore, cooperation between teachers and the school environment is needed to cultivate a literacy culture through more engaging learning activities, effective classroom management, and strengthened reading motivation.